Marketing of food and beverage in Brazil: scientific literature review on regulation and self-regulation of advertisements - Aline Kassahara; Flavia Mori Sarti (Faculdade de Medicina de Botucatu (Unesp), 2017)
The effects of marketing strategies for promotion of foods and beverages have been investigated due to its potential impacts on populations' food choices, particularly among children and adolescents. The paper presents an academic literature review on regulation and self-regulation of food and beverage advertisements in Brazil, based on search performed in electronic databases. Majority of studies were based on law analysis or qualitative study of advertisements. There are sufficient evidences on the need for government regulation of advertisements addressed to children and adolescents complementarily to institutional self-regulation in order to tackle ethical transgressions on food and beverage advertisements identified in Brazil. Additionally, there should be imposition of rigorous penalties for noncompliance to ethical rules and proposition of incentives towards actions encouraging healthy food consumption patterns, in order to comprise an actual system for promotion of public health.